Movimentos de (trans) formação na Amazônia legal: a educação em ciências e matemática - MATOS, Maria da Conceição Gemaque de (Universidade Federal do Pará, 2017)
This work research students from graduate Programs in Education and Science and Mathematics in the Legal Amazon, the time interval from 2002 to 2012. It is a qualitative research, in narrative form, with the objective to analyze to understand in what terms set and to express their attitudes, actions, and utopias of teacher trainers alumni of graduate programs in Education in Science and Mathematics in the Legal Amazon, working directly or indirectly in the teacher training process. Therefore, I investigate the first two programs implemented in the region that through the published dissertations and Lattes curriculum of the graduates to demarcate the investigative trends of the programs and the professional field of action that are distributed. I considered the Lattes curriculum as the academic and professional biography of each graduate, and, took as a reference to map the educational space in which each one is inserted. The survey went on to give voice to thirteen (13) graduates who work as teacher educators in Science and Mathematics thus bringing visibility to the narrator role of each subject, in order to register the particularities and peculiarities of their stories in the training process and professional practice. I considered the narrative research as a way to outline the experiences revealed in the set of articulated accounts in the Amazonian socio-cultural context in driving actions of (trans) formation movements in science and mathematics education. In the appropriation of the voices of the subjects I found life stories of the personal and social construction of each traversing (trans) formations driven by utopias, explicit or implicit, which originated in the incompleteness perceived by each subject. The deconstruction of narrative texts of the graduates and the reconstruction of metatext were conducted by discursive textual analysis looking ahead three axes of analysis. Each interview enabled the subject the (self) training reflection in the movement to look at themselves to describe their training paths, and also revealed their actions seeking to (trans) form the training of teachers in science and mathematics in the Amazon. The feeling of incompleteness of graduates, coupled with the utopias, procured in each subject the construction and implementation of changes, requiring the need to understand the ground in which each one was, and thus, become able to dare and to introduce new meanings for education in science and mathematics.